2010
DOI: 10.1111/j.1476-5381.2010.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography of [18F]‐big endothelin‐1 reveals renal excretion but tissue‐specific conversion to [18F]‐endothelin‐1 in lung and liver

Abstract: Background and purpose: Big endothelin-1 (ET-1) circulates in plasma but does not bind to ET receptors until converted to ET-1 by smooth muscle converting enzymes. We hypothesized that tissue-specific conversion of [ ]-big ET-1 was rapidly cleared from the circulation (t1/2 = 2.9 Ϯ 0.1 min). Whole body microPET images showed highest uptake of radioactivity in three major organs. In lungs and liver, time activity curves peaked within 2.5 min, then plateaued reaching equilibrium after 10 min, with no further dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…In a preliminary study, we found that the vasoconstrictor effect of Big ET progressed after cessation of the infusion and stabilized after ϳ5 min. This delay was most likely due to the necessary conversion of Big ET into the vasoactive ET and is in accordance with the 3-min half time of uptake of Big ET into endothelial cells (10). The measurements of the vascular effects of Big ET were, therefore, performed 10 min after cessation of its infusion.…”
Section: Exercise-induced Modulation Of the Et System In The Coronarymentioning
confidence: 98%
“…In a preliminary study, we found that the vasoconstrictor effect of Big ET progressed after cessation of the infusion and stabilized after ϳ5 min. This delay was most likely due to the necessary conversion of Big ET into the vasoactive ET and is in accordance with the 3-min half time of uptake of Big ET into endothelial cells (10). The measurements of the vascular effects of Big ET were, therefore, performed 10 min after cessation of its infusion.…”
Section: Exercise-induced Modulation Of the Et System In The Coronarymentioning
confidence: 98%
“…A major challenge in imaging is to translate results from florescent probes in vitro to in vivo. Ortolano et al (2010) image fluorescent labelled lymphocytes in an animal model of stroke and Johnström et al (2010) report the use of PET to dynamically image receptors in vivo within target organs, utilising the conversion of the inactive precursor of endothelin-1 to the active form. Finally, anticipating the new era of regenerative medicine, Baril et al (2010) review strategies for non-invasive imaging of gene therapy, to allow the precise spatiotemporal measurement of gene expression particularly in longitudinal studies involving gene transfer vectors.…”
Section: Bjp British Journal Ofmentioning
confidence: 99%
“…Ortolano et al . (2010) image fluorescent labelled lymphocytes in an animal model of stroke and Johnström et al . (2010) report the use of PET to dynamically image receptors in vivo within target organs, utilising the conversion of the inactive precursor of endothelin‐1 to the active form.…”
mentioning
confidence: 99%
“…ECE activity is increased in endothelium-denuded human vessels with atherosclerosis (Maguire and Davenport, 1998) suggesting that conversion of big ET-1 to ET-1 by smooth muscle ECE may contribute to increased plasma/tissue ET levels in disease. Conversion has been imaged in vivo by infusion of [ 18 F]-big ET-1 to quantify tissue specific conversion to [ 18 F]-ET-1 which bound to ET A receptors on the vascular smooth muscle (Johnstrom et al, 2010). This was significantly reduced by phosphoramidon, an inhibitor of ECE and NEP, which does not cross the plasma membrane and therefore cannot inhibit endothelial cell ECE but is consistent with inhibition of enzyme conversion by vascular smooth muscle and subsequent reduction of [ 18 F]-ET-1 receptor binding (Johnstrom et al, 2010).…”
Section: Introductionmentioning
confidence: 99%